Arbitration in international tax law: Legal obstacles to agreeing - Popović Dejan; Ilić-Popov Gordana (Anali Pravnog Fakulteta u Beogradu)
Article 25 (5) of the OECD Model Convention contains a provision that defines the failure of the mutual agreement procedure to solve a dispute whether a person has been taxed in a manner that is not in accordance with the provisions of the Convention within two years as a deferred condition for activating the arbitration clause. The parties in arbitration are the Contracting States rather than the taxpayer who initiated it. Despite the advantages of the arbitration dispute resolution, numerous developing countries do not accept the arbitration clause stating that it would violate their fiscal sovereignty from two reasons. Firstly, the authors point out that relying on the 'baseball arbitration' would diminish the relevance of the objection that arbitration jeopardises administrative independence. Secondly, the objection that the state cannot renounce its right to tax is also untenable since it overlooks the difference between the state's sovereign inalienable right to introduce tax and its right to collect a disputed amount. Neither remaining two constitutional-law arguments are valid. From the point of view of the rule of law principle, there is no justification to confine arbitration only to the issues concerning the interpretation of facts. From the point of view of the principle of equality, the constitutional courts will not require symmetrical access to arbitration in domestic tax disputes since they tend to interpret this principle in the manner that it applies to the persons in the same or similar legal situations - namely, to those who meet the requirements for arbitration stipulated in a tax treaty. The authors conclude that Serbia should reassess its negative attitude on tax arbitration, which will make it easier for her to deal with the obligation emerging in the accession negotiations to adopt the EU Arbitration Convention as a part of the acquis.